Internacionalização do currículo da medicina em contextos emergentes : um estudo de caso da Unipampa - Abad, Lucas Gonçalves (2019)
This dissertation discusses the conceptions of Internationalization of the Curriculum (IoC) and its relation with the actions carried out in universities inserted in emerging contexts, aiming to identify in the curriculum of the undergraduate course in Medicine of UNIPAMPA the actions of IoC as its influences in the university environment. Given that in the globalized society there are multiple cultural, economic and technological influences, since IoC is an integrated process to such influences and through which the individual's learning in a broad dimension is sought, the research identifies, in the assumptions of Leask (2011) that IoC is composed of international activities that qualify the formal and informal curriculum in the search for professional training for a Global Citizenship (UNESCO, 2015). Through an empirical study, with a qualitative approach, the applied research using a case study that analyzed the course of Medicine of the Federal University of Pampa (UNIPAMPA), was used several data collection procedures (interviews, bibliographical and documentary) to meet the specific objectives of the present study. Thus, through the state of knowledge methodology (MOROSINI, 2015), it was possible to identify the state of knowledge in the recent production of theses and dissertations, leading to the identification of two initial categories that were the focus of the other analysis procedures. Interviews conducted with four managers of UNIPAMPA, through the Discursive Textual Analysis (MORAES and GALLIAZZI, 2016), were analyzed starting from the initial categories "internationalization focused on professional formation" and "internationalization policies", where one can evaluate the perception of managers the existence of actions of IoC in the course of Medicine of the University, so that the results indicate that UNIPAMPA meets the proposals for an internationalized curriculum from the typologies of OECD and EAIE. The research also identified, through the analysis of the Institutional Development Plan (PDI) and the Pedagogical Project of the Course (PPC) of Medicine of UNIPAMPA, the institutional policies that provide the existence of these IoC actions in the curriculum studied, identifying the existence of propositions related to internationalization, due to its peculiar characteristic of multicampia in frontier region. Although the institution has 80% of its campuses installed in the border region and the campus, the object of this study is part of this quantitative, it is inserted in a university perspective in emerging contexts, since it occupies a space of transition between traditional and contemporary models (MOROSINI, 2014). Thus, although the institutional documents analyzed and the report of the managers demonstrate to actions of internationalization of the Medicine curriculum in UNIPAMPA, promoting these with the contribution of active methodologies appropriate to the context of the University and to the context of the curriculum that is part of a proposal (paradigm of integrality), the challenges to strengthening and existing relations between policies and actions of internationalization of the curriculum are present at this juncture and are demonstrated through the analysis of the internal and external environment, as to the positive and negative aspects dimensioned in the SWOT Matrix presented at the end of this study.